Living the everyday life of internationalization : Russian academic teachers experiences of internationalization in higher education - Annerblom, Marie-Louise (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2012)
The aim of this study has been to study the academic teachers’ understanding and their experiences of internationalization in relation to the current efforts to internationalize higher education. Participation in international projects, the increase of student and teacher mobility and also the strong concern of policy writing about internationalization has caused the need to know more about the acquired experiences of internationalization. What do we learn by taking part in international activities and what do we know by living ”the everyday life of internationalization”? A qualitative study was done, we interviewed seven academic teachers coming from state and private Russian universities that had experience from international activities. The results were analysed by reflexive methodology related to theories about the culture of globalisation, a conscious critical dialogue, transformative learning and a need for competence development among academic teachers.A recurring result was the notion that universities in different countries applied different strategies towards the internationalisation process. Another result was that from one international university to another not only did the relationship between students and their teachers differed but also in how they went discussing about these experiences. Another shared outcome among the academic teachers was their experiences of selfdevelopment and professional development. Differences between the teacher’s experiences of internationalization seemed to be based upon specific individual experiences of internationalization like e.g. if they had worked in international projects, taken care of student exchanges or if they themselves had worked or visited other universities in other countries. The relevance of this study to Nordic educational research is the inclusion of Russian academics from the Barents region into research about internationalization in the northern region. Godkänd; 2012; 20120327 (ysko)